Lean Canvas and the Business Model Canvas Model in Startup Piecework - Razabillah, Nurlaela; Putri Junaedi, Sausan Raihana; Maria Daeli, Ora Plane; Arasid, Nova Syahrani (Pandawan Sejahtera Indonesia, 2023)
A newcomer in the social media industry, Piecework is dedicated to assisting small businesses in growing their operations in the age of globalization. Having the appropriate business model for a simple explanation of a company's business idea is essential when creating a startup. The Business Model Canvas was a business model that startups utilized frequently at first, but following the creation of the Lean Canvas, they were interested in using it for company development. The purpose of the comparison between the Business Model Canvas and Lean Canvas in the Piecework startup is to enhance the startup development strategy, gain a stronger market position, and gain a deeper understanding of the business framework based on both business models. To validate the concerns encountered, ten informants were interviewed using a qualitative methodology. Lean Canvas is thought to be more suitable for usage by Piecework because using Lean Canvas, Piecework may build services that are more suitable for customers, according to the comparison of the Business Model Canvas and Lean Canvas business models.